Phylogeny, Diversification, and Biogeography of Garra (Cypriniformes: Cyprinidae) Reveals Multiple Cross‐Drainage Dispersals in Southeast Asia - Zhi‐Bang Wang; Thaung Naing Oo; Lan‐Ping Zheng; Xiao‐Yong Chen (Ecology and Evolution)
ABSTRACT Garra, a kind of small‐ to medium‐sized fish, is widely distributed from southern Eurasia to central Africa. As one of the most diverse genera of Cyprinidae, investigating the phylogeny and biogeography of Garra remains challenging. In this study, we combined sequences of Garra samples collected from Myanmar with sequences downloaded from GenBank to investigate the phylogeny, diversification, and biogeography of Garra on a global scale, with an emphasis on Southeast Asia. Species delimitation results indicated that there are at least 22 potential species, including eight undescribed species in Myanmar, suggesting that the diversity of Garra in this region have been largely underestimated. Diversification analysis suggested a relatively high diversification rate in the early branches of Garra. Ancestral distribution reconstruction results revealed that Garra originated from the Irrawaddy River basin in the late Eocene, approximately 34 million years ago, with subsequent dispersals across different drainages influenced by the uplift of the Qinghai‐Tibet Plateau. Our study provided a new insight into the evolutionary history of Garra and the basis for further research on this genus.